Communication from the governor of Virginia enclosing resolutions of state of Tennessee relative to opening southern ports : December 16, 2018 (Document (Virginia. General Assembly. Senate), 1861)
1861 Tennessee resolutions which supported a policy of opening southern ports to international commerce. Upon receipt from Tennessee Governor Isham G. Harris, the resolutions were submitted by Virginia Governor John Letcher to the Virginia General Assembly.